2017
DOI: 10.1080/15569527.2017.1354217
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the effect of aflibercept loading dose on the retinal vessel diameters in patients with treatment-naive neovascular AMD

Abstract: The current study showed that IVA led to significant retinal arteriolar vasoconstriction and choroidal thinning, which may cause reduced retinal blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…However, these studies investigated changes in retinal vessel diameters only one week to month after single or monthly repeated IVI, when intraocular pressure was not altered anymore. Most of the studies observed a long-term reduction in retinal artery diameter (Soliman et al 2008;Papadopoulou et al 2009;Sacu et al 2011;Corvi et al 2015;Kurt et al 2017;Consigli et al 2018;Tetiko glu et al 2018). Tatlipinar et al repeatedly measured retinal vessel diameters of DME and CNV eyes before and during the first week after IVI with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies investigated changes in retinal vessel diameters only one week to month after single or monthly repeated IVI, when intraocular pressure was not altered anymore. Most of the studies observed a long-term reduction in retinal artery diameter (Soliman et al 2008;Papadopoulou et al 2009;Sacu et al 2011;Corvi et al 2015;Kurt et al 2017;Consigli et al 2018;Tetiko glu et al 2018). Tatlipinar et al repeatedly measured retinal vessel diameters of DME and CNV eyes before and during the first week after IVI with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…; Tetikoglu et al. ). We speculate that the vasoconstriction of retinal vessels demonstrated in this study following intravitreal injection of aflibercept is probably in truth a mere reversal of the vasodilative effect of VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…Lately, another paper reported significant vasoconstriction of the retinal arterioles after three monthly injections of aflibercept using a computer‐based approach (Tetikoğlu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, choroidal thickness has lately been shown to decline in patients with AMD following three injections of aflibercept (Tetikoğlu et al. ). As expected, we observed transient rise in IOP, but no correlation with the amount of reflux was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation